1979
DOI: 10.1159/000122935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphine and Naloxone on Serum Levels of Luteinizing Hormone and Prolactin in Prepubertal Male and Female Rats

Abstract: The effects of morphine (M) and naloxone (N) on serum levels of luteinizing hormone (LH) and prolactin (PRL) in prepubertal male and female rats were investigated. N raised serum LH concentrations in female rats at 10, 15, 20, 25 and 30 days of age, but increased serum LH levels in male prepubertal rats only at 30 days of age. M significantly depressed serum LH values in both sexes only at 15 days of age. M increased serum PRL levels in immature rats of both sexes in all age groups, except in 25-day-old males,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
45
1

Year Published

1981
1981
1992
1992

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(53 citation statements)
references
References 10 publications
(21 reference statements)
7
45
1
Order By: Relevance
“…This agrees with results of a similar study in early to mid-pubertal boys reported recently (28). Animal studies have shown a sex-dependent difference in the effect of naloxone on LH secretion: opiate antagonism increased LH in prepubertal female rats but had little effect in prepubertal male rats (2,13). In contrast, the present study showed no change in gonadotropin secretion during naloxone in the prepubertal girl as well as in the late pre-and early pubertal boys.…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with results of a similar study in early to mid-pubertal boys reported recently (28). Animal studies have shown a sex-dependent difference in the effect of naloxone on LH secretion: opiate antagonism increased LH in prepubertal female rats but had little effect in prepubertal male rats (2,13). In contrast, the present study showed no change in gonadotropin secretion during naloxone in the prepubertal girl as well as in the late pre-and early pubertal boys.…”
Section: Discussionsupporting
confidence: 93%
“…Reduction of hypothalamic norepinephrine synthesis by a-M PT or DDC, or blockade of the a-receptors by PBH, resulted in complete suppression of N AL-induced LH release. These results suggest that the N AL-induced increase in LH release is mediated in part via a hypothalamic noradrenergic mechanism.Our laboratory reported that naloxone hydrochloride (NAL), a specific opiate antagonist, not only blocked the inhibitory action of morphine on luteinizing hormone (LH) release, but when administered alone, stimulated LH and follicle stimulating hormone release [5], This effect of NAL on LH release has been confirmed in intact male and female rats [3,6,14], in castrated male rats [34], and in human sub jects [23]. We have suggested that LH release is under tonic inhibition by hypothalamic opioid peptides [21].…”
mentioning
confidence: 99%
“…However, response to naloxone did not change during sexual maturation in these ewe lambs. In other studies with prepubertal ewe lambs, administration of naloxone increased LH concen¬ tration in circulation at 20, 25 and 30 weeks of age but had no effect at 5, 10 and 15 weeks of age (Rawlings & Churchill, 1990 (Ieiri et al, 1979;Bhanot & Wilkinson, 1983b;Sylvester et al, 1985). An age-related decrease was observed in the ability of a met-enkephalin analogue to inhibit secretion of LH in immature female rats (Bhanot & Wilkinson, 1983b).…”
Section: Discussionmentioning
confidence: 78%